2019
DOI: 10.1016/j.cub.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Non-Crh Glutamatergic Neurons in Barrington’s Nucleus Control Micturition via Glutamatergic Afferents from the Midbrain and Hypothalamus

Abstract: with data analysis, Lian Guo for help with cystometry, Arjan Gijsberts (IIT, Genova IT) for custom MATLAB scripts and codes, Michael Lazerus and Patrick Fuller (BIDMC, Boston USA) for generating the AAV-DIO-DTA construct and vector, and Pavlos Gorelik (HMS-instrumentation core facility, Boston USA) for help with generating behavior cages. We especially acknowledge Patrick Fuller for his advice and constructive criticism of early versions of this manuscript, Brad Lowell and Clif Saper, and members of the labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 66 publications
(96 reference statements)
2
59
0
Order By: Relevance
“…In rats and mice, Bar CRH neurons make up roughly half of all Bar neurons that project axons to the sacral spinal cord ( Valentino et al, 1995 ; Verstegen et al, 2017 ). Optogenetic and chemogenetic experiments shows that Bar CRH neurons promote bladder contraction ( Hou et al, 2016 ; Keller et al, 2018 ; Verstegen et al, 2019 ). Other recent studies verify that optogenetic stimulation of Bar CRH neurons drives bladder contraction, but typically does not result in urinary excretion ( Ito et al, 2020 ; Verstegen et al, 2019 ).…”
Section: Barrington’s Nucleus Synchronizes Bladder Contraction and Spmentioning
confidence: 99%
“…In rats and mice, Bar CRH neurons make up roughly half of all Bar neurons that project axons to the sacral spinal cord ( Valentino et al, 1995 ; Verstegen et al, 2017 ). Optogenetic and chemogenetic experiments shows that Bar CRH neurons promote bladder contraction ( Hou et al, 2016 ; Keller et al, 2018 ; Verstegen et al, 2019 ). Other recent studies verify that optogenetic stimulation of Bar CRH neurons drives bladder contraction, but typically does not result in urinary excretion ( Ito et al, 2020 ; Verstegen et al, 2019 ).…”
Section: Barrington’s Nucleus Synchronizes Bladder Contraction and Spmentioning
confidence: 99%
“…The traditional answer has been mum. Mothers modify the incubation conditions of their offspring in a variety of ways, including via maternal nest site choice at oviposition or via sophisticated thermoregulatory behaviour prior to oviposition (e.g., [3,4]).…”
Section: Dispatchesmentioning
confidence: 99%
“…Today it is widely accepted that the pons contains a neural circuit that regulates lower urinary tract function, but how does it accomplish this? In a study reported in a recent issue of Current Biology, Verstegen et al [3]. have skillfully used the latest tools of modern neurobiology to answer some very basic questions about the functional role of Barrington's nucleus; their findings contribute to a better understanding of the mechanism(s) of central neural control over lower urinary tract function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PMC, including both the Crh-expressing and sphincter-controlling neurons, receives inputs from distributed circuits across the brain which presumably carry proand anti-micturition information that is processed in the PMC (Hou et al, 2016;Verstegen et al, 2019;Yao et al, 2018). Thus, PMC serves as a suitable starting point to retrogradely map the neural circuitry by which information is integrated to trigger a specific motor action.…”
Section: Introductionmentioning
confidence: 99%